2016
DOI: 10.1007/s11701-016-0569-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a robotics curriculum at an academic general surgery training program: our initial experience

Abstract: The robotic surgical platform is being utilized by a growing number of hospitals across the country, including academic medical centers. Training programs are tasked with teaching their residents how to utilize this technology. To this end, we have developed and implemented a robotic surgical curriculum, and share our initial experience here. Our curriculum was implemented for all General Surgical residents for the academic year 2014-2015. The curriculum consisted of online training, readings, bedside training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…According to older studies, most programs used experiences assisting in the operating room as the main teaching method for residents, with minimal augmentation from teaching labs and conference/didactic session [ 5 , 9 , 10 ]. The results of this study do not support this result and, along with more recent studies, found that many programs have now switched to using a combination of teaching methods to educate residents in robotics [ 14 , 15 ]. This difference may be due to the fact that robotics technology is rapidly developing, with more developed and accessible simulation training tools.…”
Section: Discussioncontrasting
confidence: 88%
“…According to older studies, most programs used experiences assisting in the operating room as the main teaching method for residents, with minimal augmentation from teaching labs and conference/didactic session [ 5 , 9 , 10 ]. The results of this study do not support this result and, along with more recent studies, found that many programs have now switched to using a combination of teaching methods to educate residents in robotics [ 14 , 15 ]. This difference may be due to the fact that robotics technology is rapidly developing, with more developed and accessible simulation training tools.…”
Section: Discussioncontrasting
confidence: 88%
“…In other specialties such as urology, training schemes for robotic surgery have been described, although there is still a recognised need for a structured, standardised curriculum and robust credentialing guidelines for proficiency [28][29][30][31][32][33]. To our knowledge, in colorectal surgery three studies discuss a training pathway for robotic surgery [18,34,35], but only include a relatively small number of surgeons and cases. This study examines the outcomes of 1130 robotic colorectal cases across 26 centres in Europe and its results suggest that the EARCS programme facilitates safe and effective training of robotic colorectal surgery while ensuring good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 96% of participants enrolled in the curriculum successfully completed all components in 9-17 h and reached proficiency after a mean of 72 repetitions. A more recent study of implementation of a standard robotics curriculum in general surgery combined traineedirected and expert-directed learning utilizing a wide variety of training modalities [16]. Ultimately, all participants (N = 20) completed the curriculum and 65% of participants reported sitting at the surgeon console.…”
Section: Discussionmentioning
confidence: 99%